Music Genre Classification (International Journal of Engineering and Computer Science, 2015)
The purpose  of this research is to build  a machine learning model to predict  the genre of a song. This paper  analyzes a song as a wave and determines the factors involved and predicts the  genre.  Application  of the  model  is primarily to automatize the process  of genre  identification  which shall aid in building  of music recommendation systems.